(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
The article provides information about some representatives of the Iridaceae Juss. grown in the Gareev Botanical Garden of NAS KR, their ability to vegetative and seed reproduction, the value and sustainability of cultivation in the culture of the botanical garden.